Estudo meta-analítico sobre imagem de país e suas relações - Oliveira, Shirlei Cristiane de (Universidade do Vale do Rio dos Sinos, 2022)
This work addresses the issue of country image through a meta-analysis that considered 1328 works from 1970 to 2021. Considering the research carried out through the main scientific bases Google Scholar, Taylor & Francis, Emerald Insight, Science Direct and JSTOR, we identified the relationships antecedent and consequent between country image and purchase intention. The meta-analysis was conducted through a systematic literature review where it was possible, after refinements, to reach 43 works as a final sample, totaling 59 related effects and 21,013 subjects. The consequent relationships involving CI were: purchase intention, product quality, brand image and loyalty. As an antecedent, ethnocentrism was identified, which did not result as significant in the relationship with IC. A significant effect was found in the relationship between CI and purchase intention, being moderated by the degree of internationalization of the countries analyzed. It was also observed that the vast literature still diverges from the definition of the country image theme, confusing in many studies with concepts of country of origin effect (COO). The following definition was proposed for country image: country image refers to general perceptions, including opinions, beliefs and ideas of a country, associated with affective and cognitive aspects that form stereotypes based on political development structures, economic, technological, social, cultural and environmental of a nation. With this definition, it was possible to contribute to the literature, as well as to clarify the understanding and difference between CI and country of origin effect (COO). Since COO refers exclusively to products, or the origin of the country of the product. However, there were many other identified constructs that were not related due to the low incidence in primary studies. From a managerial point of view, which also serves public managers, we collaborate with commercial approaches and perspectives for disseminating the country's image, which has proven to generate greater consumer interest in buying, and we conclude with suggestions for future studies.
Keywords: Metanálise; Imagem de país; Intenção de compra; Moderadores; Meta-analysis; Country image; Buy intention; Moderators; ACCNPQ::Ciências Sociais Aplicadas::Administração